Constraining the nature of two Lyα emitters detected by ALMA at z = 4.7. Issue 2 (15th February 2014) - Williams, R. J.; Wagg, J.; Maiolino, R.; Foster, C.; Aravena, M.; Wiklind, T.; Carilli, C. L.; McMahon, R. G.; Riechers, D.; Walter, F.
Abstract : We report optical spectroscopy from the Very Large Telescope/FOcal Reducer and low dispersion spectroscopy of the two Lyα emitters (LAEs) companions to the quasi-stellar object–sub-millimetre galaxy system BRI1202-0725 at z = 4.7, which have recently been detected in the [C ii ]158 μm line by the Atacama Large Millimetre/Sub-millimetre Array. We detect Lyα emission from both sources and so confirm that these LAE candidates are physically associated with the BRI1202-0725 system. We also report the lack of detection of any high-ionization emission lines (N v λ1240, Si iv λ1396, C iv λ1549 and He ii λ1640) and find that these systems are likely not photoionized by the quasar, leaving in situ star formation as the main powering source of these LAEs. We also find that both LAEs have Lyα emission much broader (∼1300 km s −1 ) than the [C ii ] emission and broader than most LAEs. In addition, both LAEs have roughly symmetric Lyα profiles implying that both systems are within the H ii sphere produced by the quasar. This is the first time that the proximity zone of a quasar is probed by exploiting nearby LAEs. We discuss the observational properties of these galaxies in the context of recent galaxy formation models.